Answer:
The turning point is (-2,10)
Step-by-step explanation:
we have
[tex]y=6-4x-x^{2}[/tex]
This is a quadratic equation (vertical parabola) open downward
we know that
The turning point of a quadratic equation is the vertex
so
Convert the quadratic equation into vertex form
[tex]y-6=-4x-x^{2}[/tex]
[tex]y-6=-(x^{2}+4x)[/tex]
[tex]y-6-4=-(x^{2}+4x+4)[/tex]
[tex]y-10=-(x^{2}+4x+4)[/tex]
[tex]y-10=-(x+2)^{2}[/tex]
[tex]y=-(x+2)^{2}+10[/tex] ----> equation in vertex form
The vertex is the point (-2,10)
therefore
The turning point is (-2,10)